Law and Human Rights: Building Collective Awareness - Apriliani, Rintan Purnama Ayu (Lex Scientia Law Review, 2017)
In Indonesia, the term, meaning and interpretation of Human Rights (HAM) is not something new among the people. Since Indonesia's independence, there has been documentation of the Indonesian nation's struggle for independence which has contained the values and principles of Human Rights (HAM) in fighting for Indonesian independence. Apart from being listed in the 1945 Constitution of the Unitary State of the Republic of Indonesia, Indonesia has also expressed a high commitment to various human rights instruments. Even Indonesia also has its own provisions regarding human rights, namely Law no. 39 of 1999 concerning Human Rights (HAM). In the provisions of Article 1 of Law no. 39 it is stated that human rights are a set of rights that are inherent in the nature and existence of humans as creatures of God Almighty and are His gifts that must be respected, upheld and protected by the rule of law, the government and everyone for the sake of respect and protection of human dignity.